2011 Sixth IEEE International Symposium on Electronic Design, Test and Application 2011
DOI: 10.1109/delta.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Software Optimization on Variable Lifetimes in a Microprocessor-Based System

Abstract: Assessing and improving the level of system robustness with respect to soft errors has become one of the main design challenges, especially when designing critical embedded systems. In systems using microprocessors (e.g. most of SoCs) the system dependability is strongly correlated with the variable lifetimes. In this paper, we discuss the impact of compilation optimizations on the lifetimes in both memory blocks and internal processor registers. Evaluations on many significant examples show that specific opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Again, it was found that the patricia application was the one with the highest reduction in the AVF at 13%. Bergaoui and Leveugle (2011) analyzed the impact of compiler optimizations on data reliability in terms of variable liveness. Liveness of a variable is the time period between the variable that is written and it is last read before a new write operation.…”
Section: Related Workmentioning
confidence: 99%
“…Again, it was found that the patricia application was the one with the highest reduction in the AVF at 13%. Bergaoui and Leveugle (2011) analyzed the impact of compiler optimizations on data reliability in terms of variable liveness. Liveness of a variable is the time period between the variable that is written and it is last read before a new write operation.…”
Section: Related Workmentioning
confidence: 99%
“…In [17] the authors analyze the impact of compiler optimizations on data reliability in terms of variable liveness. Liveness of a variable is the time period between the variable is written and it is last read before a new write operation.…”
Section: Related Workmentioning
confidence: 99%